Development of Future Planning Skills through Problem-Based Learning at Pusat Kegiatan Belajar Masyarakat/PKBM (Community Learning Activity Center) Alam Jingga, Indonesia - Robianti, Febi; Muraina Kamilu Olanrewaju; Nauriana; Sariyati (Jurnal Pembelajaran Inovatif, 2025)
This qualitative descriptive study explored the impact of Problem-Based Learning (PBL) on the development of future planning, self-directed learning, and essential life skills among eight grade X students at PKBM Alam Jingga, Indonesia. Over a two-week intervention, participants engaged in collaborative PBL sessions addressing real-life scenarios, including career decision-making, financial planning, and community development. Data from observations, journals, presentations, and interviews were analyzed thematically to identify patterns in goal-setting, problem-solving, and coping strategies. Findings reveal that PBL enhanced students’ critical thinking, self-confidence, adaptability, teamwork, and communication, while fostering holistic development by integrating cognitive, social, and emotional learning. Despite limitations, the study highlights PBL as a transformative pedagogical approach that prepares learners for academic, professional, and lifelong challenges.